Governing the waters of southern Africa. Institutionalisation and negotiation of international orders in regional freshwater governance. - (:unkn) unknown (My University, 2023)
This research studies the institutionalisation of a regional order devoted to the governance of freshwater in southern Africa. It questions the logics of multilateralism and regionalisation in the case of a sectoral bureaucracy. The first part of the dissertation explores the interpenetration of (inter)national orders and social spaces that define a Southern African water order as an interstitial and dependent space, at the crossroads of national fields of power and an international water development community. This situation leads to the establishment of a bureaucracy defined by uncertainty and the personalisation of relations between its members. In the second part, the dissertation examines how these regional agents assume their role. The study of procedures and the formalisation of practices allows here to observe the anchoring and articulation of both contempt and domination to which they are subjected by the dominant social orders (national fields of power and the international water development community). At the same time, the day-to-day informalisation of their interactions conceals the political dimension of their work, while at the same time reinforcing regional power relations. Finally, observing the social conditions of loyalty in this regional order makes it possible to take a fresh look at affinities of status, in contrast with the common reading of an individualisation of social relations in international expert circles. Through their practices, the agents negotiate the injunctions and constraints imposed on them, and thus make it possible for their regional order to endure, while at the same time securing them a social position.
Keywords: African Research